Confirmatory tests for the diagnosis of primary aldosteronism: A systematic review and meta‐analysis. (26th February 2019) - Wu, Sicen; Yang, Jun; Hu, Jinbo; Song, Ying; He, Wenwen; Yang, Shumin; Luo, Rong; Li, Qifu
Summary: Objective: Saline infusion test (SIT), captopril challenge test (CCT), fludrocortisone suppression test (FST) and oral sodium loading test (SLT) are recommended by the Endocrine Society's Clinical Practice Guidelines to diagnose primary aldosteronism, but which one is the best remains controversial. We aimed to summarize the available comparative data and evaluate the diagnostic accuracy of these four tests. Design: We searched PubMed, Embase and the Cochrane Library for relevant studies published between January 1980 and January 2018. Patients: Eligible studies reported on the accuracy of one or more of the four confirmatory tests in patients suspected of PA. Measurements: Two reviewers independently conducted the data extraction of all selected studies, which consisted of study characteristics and data to estimate the summary receiver operating characteristic (SROC) curve and the corresponding summary area under the curve (SAUC), pooled sensitivity and specificity, diagnostic odds ratios (DOR) with 95% confidence interval (CI). Results: We identified 26 articles including 3686 patients. Fifteen articles evaluated the diagnostic accuracy of CCT, 10 of SIT, 1 of FST and none of SLT. For CCT, the SAUC was 0.9207, and the pooled sensitivity and specificity were 0.87 (95% CI: 0.84‐0.89) and 0.84 (95% CI: 0.81‐0.86), respectively. For SIT, the SAUC was 0.9232, and the pooled sensitivity and specificity were 0.85 (95% CI: 0.82‐0.87) and 0.87 (95% CI: 0.85‐0.89), respectively. For FST, the pooled sensitivity and specificity were 0.87 (95% CI: 0.66‐0.97) and 0.95 (95% CI: 0.82‐0.99), respectively. Overall, we found no significant differences in the diagnostic accuracy of CCT and SIT. Conclusions: CCT and SIT exhibit high and comparable accuracy for diagnosing PA. CCT may be a more feasible alternative as it is safe and much easier to perform.